ANALISIS KINERJA KEUANGAN DAN RASIO KECUKUPAN DANA PADA DANA PENSIUN PEMBERI KERJA MANFAAT PASTI DI INDONESIA - Anggraeni, Kurnia Agustina (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2012)
Each year the Association of Pension Funds awarded to the pension fund isconsidered to have the best possible performance in furthering the pension fund as alegal entity in a professional manner to create a state fund adequacy ratio > 120% ofthe pension fund adequacy ratio has been met. This is done so that pension benefitpayments made to the amount, timing and the right people. This study aims toempirically prove the difference in financial performance of pension fund employerdefined-benefit ratio in Indonesia on the adequacy of the funds that have not been metwith funding adequacy ratios are met and the influence of age pension fund adequacyratio has been met. Research conducted on the entire population of employer pensionbenefit plan in Indonesia to submit financial and investments statements and reportsto the Bureau of Pension Fund. Statistical methods used to test the researchhypothesis is a test Mann Whitney / U test and regression analysis. The resultsshowed in 2008 until 2010 there were significant differences in financial performancein the form of Return On Investment, Operational Cost Efficiency and InvestmentPortfolio Optimization and shown with better conditions in employer pension fundswith defined benefit funds adequacy ratio has been met . And to the financialperformance of Investment Cost Efficiency with the results found significantdifferences in financial performance and demonstrated with a better state pensionfund by the fund adequacy ratios that have not been met. To the financialperformance of pension fund growth showed no significant difference. Being for thevariable age did not affect the ratio of the sufficiency of funds that have been fulfilled.Key Words: Financial Performance. Fund Adequacy Ratio, Age Pension Fund